Ocular surface diagnostics in clinical practice – from classical tests to advanced imaging - Weronika Kowalczyk; Aleksandra Snopkowska; Justyna Izdebska (Ophthalmology, 2026)
The ocular surface is a complex anatomical and functional system comprising the eyelids, conjunctiva, cornea, and overlying tear film, together with neurosensory regulatory mechanisms. Disruption of ocular surface homeostasis leads to irritation, transient visual disturbance, and epithelial alterations. The most common clinical manifestation of this process is dry eye disease [1, 2]. This paper outlines current diagnostic methods for the ocular surface, detailing a practical sequence for patient evaluation, the clinical utility of advanced imaging techniques, and the limitations of most commonly used tests. It is a review synthesizing findings from key consensus reports and review articles indexed in PubMed.